Strategic groups in a knowledge society: Knowledge elites as drivers of biotechnology development in Singapore - Thomas Menkhoff; Hans-Dieter Evers (University of Bonn, Center for Development Research (ZEF), 2005)
The objective of this paper is to examine whether the 'Strategic Group concept' is useful in understanding the evolution and rapid development of Singapore's biotechnology industries. We briefly describe the history of this new knowledge-intensive industry in Singapore, why and how it was propagated and current achievements in terms of outputs. We do also a closer look at the various organizations and actors who are involved in this ambitious state-led development initiative and the various (strategic) groups which they represent aimed at identifying some of their characteristics and patterns. The analysis suggests that the development of the industry is enabled by various more or less heterogeneous players such as (i) the Government, leading politicians, experienced civil servants and state bureaucrats with vast experiences in Singapore's powerful government-linked companies (GLCs) who are not seldom engineers by training, (ii) foreign biotechnology and life sciences experts from various countries (US, Europe) with specialized expertise and key competencies in areas such as molecular biology, chemistry, biomedicine etc. who are able to link local players with their own global networks etc. and (iii) representatives of biotechnology and life sciences industries. While the social dynamics of this vast network are poorly understood and strategic imperatives keep on shifting, it seems that the broad strategic goals outlined by Singapore's Government, namely to put Singapore's biotech cluster on the global map, are more or less shared by those involved. While more research is required to identify the antecedents and sequential patterns of strategic group formation in Singapore's biotechnology sector (i.e. network drivers such as shared interests, communication adequacy, trust and so forth), we argue that the different groups at work in this knowledge-intensive industry cluster have managed to set up an effective (temporary) strategic network alliance to achieve their various goals.
urn:nbn:de:0202-2008091151
Keywords: 330